Editorial - Chaleplioglou, Artemis (Journal of Integrated Information Management, 2024)
In the beginning, the nature of information is explored. The perspective of information in the realm of reality is explored in natural, physical, and measurement settings. Firstly, the information on natural signals versus noise is analyzed through physical measurements of speech experiments. Secondly, the information in classifying relative things into groups is analyzed by clustering flowers. A method for the selection of the appropriate number of clusters in the K-Means clustering process is presented. The following paper is a literature review on citation indexes. The published comparisons between Web of Science, Scopus, and Google Scholar have been explored through a literature survey covering the era between 2004 and 2021. The majority of works utilize multiple citation indexes in their research taking advantage of their unique features. The third paper is about the physical and digital storytelling of the Asia Minor refugees after the end of the Greco-Turkish war in 1922 in Attica, Greece. The project aims to deliver the refugees' experiences through guided tours and approaches for younger audiences, such as a coloring book, a narrative card game, and an activity book. The phygitality, the hybrid experience with augmented reality has been used as a delivery tool of heritage information. Finaly, graph databases and neural networks of large-scale data derived from social networks are presented. An IMDB dataset of movies and people contributing to a film has been used in the data modeling, querying, and graph representation paradigm.